STUDYING STUDENTS’ ABILITY TO UNDERSTAND SPEECH WITH DIFFERENT SPEEDS, ACCENTS, AND DIALECTS AND FINDING WAYS TO IMPROVE IT - Atamuradova Jasmina Jahongirovna; Sharopov Sherzod Shirinboy o‘g‘li, (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation This article examines students’ ability to understand spoken English presented at different speeds, accents, and dialects. Listening comprehension is considered one of the most challenging language skills, especially for learners who have limited exposure to authentic speech. The study analyzes common difficulties faced by students in listening activities and identifies factors that influence their comprehension, such as speech rate, pronunciation, and unfamiliar vocabulary. Furthermore, the article discusses practical teaching strategies that can help improve listening skills, including the use of multimedia resources, repeated listening practice, and exposure to various accents. The findings highlight the importance of systematic instruction and supportive classroom environments in developing students’ confidence and listening competence.